Validity and Reliability of the Stress and Anxiety to Viral Epidemics-6 (SAVE-6) Scale to Measure Viral Anxiety of Healthcare Workers in Spain During the COVID-19 Pandemic - Moraleda-Cibrián, Marta; Ahmed, Oli; Albares-Tendero, Javier; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
This study examined the validity and applicability of the Spanish version of the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) scale to healthcare workers (usually applied to the general population) to briefly measure their anxiety responses to the viral epidemic. A total of 135 healthcare workers participated in this online survey from January to July 2021. Participants’ sociodemographic characteristics were gathered, and their psychiatric symptoms were rated using SAVE-6, Goldberg Anxiety and Depression Scale (GDAS), and the Pittsburgh Sleep Quality Index (PSQI). The confirmatory factor analysis was conducted to examine the validity of the scales. The single-structure model of the SAVE-6 scale was adopted based on the results of the parallel analysis. We decided on the SAVE-6 scale, as it proved to be a good fit to measure healthcare workers' anxiety response to the viral epidemic. SAVE-6 showed good internal consistency (0.827 and McDonald’s omega = 0.834) and good convergent validity with Goldberg anxiety (r = 0.434, p< 0.001) and depression (r = 0.193, p = 0.043) scores, and PSQI score (r=0.262, p=0.002). The Spanish version of SAVE-6 is a reliable and valid rating scale to assess the anxiety response of healthcare workers specifically to the viral epidemic as a brief measure during the COVID-19 pandemic.